Surgical management of a collateral arch channel and aortic coarctation. Issue 2 (11th November 2021) - Schulick, Nicole; Lin, Yihan; Fonseca, Brian; Campbell, David N.; L. Stone, Matthew
Abstract: Background: The atretic connection between the left fourth and sixth aortic arches is a rare congenital cardiac anomaly with controversial debates on its origin. This anatomy has been previously reported with additional cardiac anomalies of maldevelopment. Aims: We present the successful surgical management of a 3‐month‐old female with Cornelia de Lange syndrome and coarctation of the aorta in the setting of this unique collateral channel. Materials & Methods: We review the beneficial utility and novelty of three‐dimensional computed tomography angiography for this anatomic lesion while also discussing the importance of multidisciplinary preoperative planning in the coordinated management of this arch anomaly and potential concomitant comorbid conditions. Results: The presented surgical case demonstrates the successful reconstruction of the aortic arch by coarctectomy with extended end‐to‐end anastomosis by a left posterolateral thoracotomy in a patient with a collateral arch channel and a hemodynamically significant aortic coarctation. Conclusion: Atretic connection between the left fourth and sixth aortic arches remains a rare congenital anomaly and may occur in the setting of an aortic coarctation. Unclear arch anatomy and indeterminant proximal aortic sizing on echocardiogram should prompt cross‐sectional imaging with computed tomography angiography to guide surgical technique selection for aortic arch reconstruction when a collateral arch channel or unique branching pattern is suspected.